2004
DOI: 10.1007/s00280-004-0830-1
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel and high-dose epirubicin as neoadjuvant chemotherapy in locally advanced breast cancer

Abstract: Docetaxel plus high-dose epirubicin showed promising activity in patients with locally advanced and inflammatory breast cancer, at the cost of moderate toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
3
5
0
8
Order By: Relevance
“…Locally advanced breast cancer with large tumor lesions and more node involvement is related with a lower pCR rate as compared with early stage or operable breast cancer [13, 14]. In the present study, the overall pCR rate (12.31%) in the PE arm was comparable to those reported previously for taxane–anthracycline-based regimens (13.3%–18%) [15, 16]. Specifically, the results were similar to those of the ABCSG-14 trial, which administered 6 cycles of epirubicin 75 mg/m 2 plus docetaxel 75 mg/m 2 , resulting in overall and breast pCR rates of 15.9% and 18.6%, respectively [17].…”
Section: Discussionsupporting
confidence: 79%
“…Locally advanced breast cancer with large tumor lesions and more node involvement is related with a lower pCR rate as compared with early stage or operable breast cancer [13, 14]. In the present study, the overall pCR rate (12.31%) in the PE arm was comparable to those reported previously for taxane–anthracycline-based regimens (13.3%–18%) [15, 16]. Specifically, the results were similar to those of the ABCSG-14 trial, which administered 6 cycles of epirubicin 75 mg/m 2 plus docetaxel 75 mg/m 2 , resulting in overall and breast pCR rates of 15.9% and 18.6%, respectively [17].…”
Section: Discussionsupporting
confidence: 79%
“…[13,14,23,24] In combination with anthracyclines pCR rates of 10% to >20% are reported depending upon the stages of tumor included in that particular study. [17,[25][26][27][28][29] As most of the trials are retrospective, have small sample size and include a heterogeneous group of patients, it is not possible to directly compare the results but the pCR and cCR in our study are in accordance with results previously reported in the literature.…”
Section: Discussionsupporting
confidence: 77%
“…The pCR rate reported from these non-randomized trials ranges from 5 to 26%; however, the definition of pCR was not uniform across these studies [20][21][22][23][24][25][26][27][28].…”
Section: Anthracycline-taxane Combinationsmentioning
confidence: 99%